Adenosine A2A and A2B Receptor Substantially Attenuate Ischemia/Reperfusion Injury in Septic rat Hearts - Busse, Hendrik; Bitzinger, Diane; Höcherl, Klaus; Seyfried, Timo; Gruber, Michael; Graf, Bernhard M.; Zausig, York A. (Cardiovascular Drugs and Therapy, 2016)
Mechanical and morphological ischemia and reperfusion (I/R) injury is reduced in septic hearts. The mechanism behind this "cardioprotection" is less well understood. As adenosine receptors play a major role for cardioprotection in non-septic hearts, we investigated the influence of adenosine receptors in a model of I/R in septic hearts.SHAM operation or cecal ligation and puncture (CLP) was performed in adult male Wistar rats (n = 60). After 24 h of incubation, hearts were isolated and randomly assigned to a group with or without adenosine receptor (Ador) antagonists (SCH 58261 and MRS 1706) administered before reperfusion. Ischemia and reperfusion lasted for 40 min each. Cardiac function of the heart was determined by measuring left ventricular pressure (LVP).Before I/R, CLP hearts showed a significant mechanical left ventricular impairment (CLP: 63 ± 5 mmHg vs. SHAM: 104 ± 6 mmHg. After I/R, left ventricular function was significantly reduced in SHAM (24 ± 32 mmHg), but not in CLP hearts (65 ± 13 mmHg). mRNA expression for the AdorA2a and AdorA2b was significantly increased in CLP, but not in SHAM hearts. LVP of CLP hearts deteriorated when AdorA2a and AdorA2b were blocked.The morphological and functional I/R injury in septic animals is less pronounced compared to non-septic animals. By a combined blockade of AdorA2a and AdorA2b this "cardioprotective" effect is nearly abolished in septic hearts. This is the first study showing, that AdorA2a and AdorA2b may play an important role for a reduced functional I/R injury in the septic heart.
EVALuna2:8527